Research on mechanism and application of compound roof cutting and pressure relief control in thick sandstone roof mining roadways - Gao, Hainan; Zhao, Shankun; Shi, Yue; Li, Yunpeng; Lv, Kun; Fu, Qiang; He, Guanghui; Ren, Weiguang; Zhou, Zhibin; Chen, Lei; Li, Haonan (Frontiers in Earth Science, 2025)
Thick sandstone roof strata exacerbate surrounding rock deformation and failure in roadways, posing a severe threat to safe and efficient coal mine production. To address the challenge of controlling surrounding rock in high-stress roadways under such conditions, a novel composite roof cutting and pressure-relief method leveraging the dilation characteristics of gangue was hereby proposed. Firstly, numerical simulations were employed to establish a gangue model, and investigations were conducted into the in-fluence of gangue size and placement patterns on its dilation behavior and bearing capacity. The results revealed that within a specific size range (excluding extreme particle sizes such as the maximum and minimum), smaller gangue particles with more irregular placement exhibited a higher dilation coefficient and superior bearing performance. Building upon this principle, the composite roof cutting and pressure-relief method was further formulated, accompanied by the development of a theoretical roof structure model elucidating its control mechanism. Secondly, numerical simulations were performed to assess the control effectiveness of the new method, and comparative analyses were carried out to verify its efficacy. The results demonstrated that this method effectively utilized gangue dilation characteristics, significantly minimizing overlying strata subsidence and alleviating surrounding rock stress on the solid coal side of the roadway. Finally, field engineering trials were conducted. Monitoring data confirmed that the new method successfully reduced surrounding rock stress, optimized the roadway stress environment, effectively suppressed surrounding rock deformation, and achieved the objective of roadway protection. Overall, the re-search findings provide significant references for controlling surrounding rock deformation in high-stress roadways under thick sandstone roof conditions.